A rare earth permanent magnet and its manufacturing method and application
By arranging the diffusion sources of Mn and heavy rare earth elements on the substrate surface of the neodymium iron boron magnet and carrying out two-stage heat treatment, the problems of high amount of heavy rare earth and insufficient diffusion depth in the prior art are solved, and a more uniform distribution of heavy rare earths and coercive force is achieved.
Patent Information
- Application Number
- CN202210800318.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-07-06
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2042-07-06
AI Technical Summary
In the prior art, when preparing neodymium iron boron magnets, it is difficult to effectively reduce the amount of heavy rare earths, resulting in high production costs, and excessive reaction between the diffusion source and the crystal grains on the surface of the magnet, resulting in an increase in the coercive force difference and insufficient diffusion depth.
By arranging a diffusion source, including Mn and heavy rare earth elements, on the substrate surface of the neodymium iron boron magnet, and performing two-stage heat treatment, the diffusion temperature and time are controlled to reduce the reaction between the diffusion source and the grains on the surface of the magnet, and improving the diffusion depth and utilization rate of heavy rare earths.
A more uniform distribution of heavy rare earths is achieved, reducing the coercive force difference between the magnet surface and core, improving the coercive force and corrosion resistance of the magnet, and reducing production costs.
Smart Images

Figure BDA0003733748380000151 
Figure BDA0003733748380000161
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of permanent magnet preparation, and in particular to a rare earth permanent magnet and a manufacturing method and application thereof. Background Art
[0002] Sintered NdFeB magnets have excellent magnetic properties and are therefore widely used. In particular, the promotion of heavy rare earth diffusion technology in recent years has further improved the comprehensive magnetic properties of NdFeB magnets, with the sum of magnetic energy product (MGOe) and coercive force (Hcj) exceeding 80. However, the heavy rare earth used in diffusion technology has a high material cost, so reducing the amount of diffused heavy rare earth is extremely important for reducing the production cost of magnets. At present, the research on improving the performance of magnets by adding diffusion aids (i.e., composite diffusion) to replace the conventional grain boundary diffusion method has been widely studied in the industry. Many researchers have also made corresponding analyses on the types of elements for adding aids, which currently mainly include two categories: ① Adding low melting point (e.g., below 1100°C) elements such as Cu, Ga, Al, Ag as auxiliary diffusion sources. Such elements often have the effect of improving grain boundary wettability and increasing Hcj in traditional sintered NdFeB magnets. When added as diffusion source auxiliary elements, the melting point of the diffusion source will be reduced. In this case, if the traditional heavy rare earth diffusion temperature is used for diffusion, the heavy rare earth diffusion source will melt rapidly at a lower temperature, the grains on the surface of the magnet will transition and fuse with the diffusion source, and the diffusion source elements will excessively penetrate into the grains on the surface of the magnet, increasing the consumption of the diffusion source elements, resulting in an increase in the difference in Hcj between the surface of the diffused magnet and the core of the magnet. Although the consumption of diffusion sources is reduced by lowering the diffusion temperature, the migration speed of heavy rare earth elements in the grain boundary phase decreases as the diffusion temperature decreases, resulting in a significant reduction in the diffusion depth, making it difficult to prepare thick diffusion magnets. Therefore, it is difficult to achieve actual beneficial effects in practical applications. ② Adding high melting point elements (e.g., above 1600°C) such as Zr, Ti, Nb, and W as auxiliary diffusion sources will increase the melting point of the diffusion source after adding such elements, making it more difficult for the heavy rare earth diffusion source to quickly penetrate into the magnet. Increasing the diffusion temperature will increase the liquid phase ratio of the magnet at high temperature, and intensify the reaction between the diffusion source and the grains on the surface of the magnet.
[0003] Therefore, selecting appropriate diffusion source additive elements and diffusion temperature process to reduce the reaction between the diffusion source and the grains on the surface of the magnet and allow more diffusion sources to penetrate into the interior of the magnet, thereby reducing the Hcj difference between the surface and core of the magnet, and achieving improved heavy rare earth utilization and diffusion depth has become a technical problem that needs to be solved urgently. Summary of the invention
[0004] To solve the above problems, the present invention provides the following technical solutions:
[0005] A rare earth permanent magnet, comprising R2T14 The main phase structure of B grains, where
[0006] R is a rare earth element;
[0007] T comprises at least Mn, Fe, and optionally a transition metal including Co;
[0008] B is boron;
[0009] The permanent magnet also includes Mn and heavy rare earth elements diffused and distributed in the grain boundaries;
[0010] The heavy rare earth element is selected from at least one of Dy, Ho and Tb.
[0011] According to an embodiment of the present invention, R is selected from Nd, and optionally contains or does not contain at least one of Pr, Dy, Tb, Ho, Ce, and Gd.
[0012] According to an embodiment of the present invention, the permanent magnet also includes M.
[0013] Preferably, M is selected from at least one of aluminum (Al), titanium (Ti), copper (Cu), gallium (Ga), zirconium (Zr), and niobium (Nb).
[0014] According to an embodiment of the present invention, in the permanent magnet, the contents of R, T, B and M are not specifically limited, and any contents known in the art may be used. Exemplarily, the weight percentage of M is 0≤M≤5%.
[0015] According to an embodiment of the present invention, the Mn content at the surface of the permanent magnet is x1, the heavy rare earth content at the surface is y1, the Mn content at 500 μm from the surface is x2, and the heavy rare earth content at 500 μm from the surface is y2, wherein x1>x2 and y1>y2. In the present invention, the Mn content refers to the total mass of Mn in the main phase structure and the grain boundary. In the present invention, the Mn content at the surface of the permanent magnet refers to the Mn content close to the surface of the permanent magnet, for example, the Mn content within 10 μm of the surface of the permanent magnet.
[0016] According to an embodiment of the present invention, the coercive force at the surface of the permanent magnet is z1, and the coercive force at the core of the permanent magnet is z2, z1>z2. In the present invention, the coercive force at the surface of the permanent magnet refers to the coercive force close to the surface of the permanent magnet, for example, the coercive force within 1 mm of the surface of the permanent magnet. In the present invention, the core of the permanent magnet refers to the geometric center of the permanent magnet.
[0017] According to an embodiment of the present invention, the thickness of the permanent magnet is m. In the present invention, the thickness of the permanent magnet refers to the length value of the permanent magnet along any diffusion direction, for example, it can be the length value of the orientation direction, the length direction or the width direction of the permanent magnet.
[0018] Preferably, the thickness m of the permanent magnet is ≤15 mm, for example, 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm, 10 mm, 11 mm, 12 mm, 13 mm, 14 mm, or 15 mm.
[0019] According to an embodiment of the present invention, the permanent magnet satisfies the following equations (1) and (2):
[0020] x1 / x2≥y1 / y2 (1)
[0021] [2*x1 / x2-(z1-z2) / 2 / m]≥0 (2).
[0022] The inventors have found that when the above equations (1) and (2) are not satisfied, the difference z1-z2 between the surface and core Hcj of the permanent magnet is too large.
[0023] According to an embodiment of the present invention, the oxygen content of the rare earth permanent magnet is below 2000ppm. In the present invention, the oxygen content of the rare earth permanent magnet is controlled to be below 2000ppm by a low oxygen process, which can effectively reduce the formation of R oxides (such as neodymium oxide) in the grain boundary and grain boundary triple point region, improve the wettability of the grain boundary of the permanent magnet, enhance the continuity of the grain boundary, and further improve the diffusion depth of the heavy rare earth element in the permanent magnet, and enhance the coercive force of the permanent magnet.
[0024] According to an embodiment of the present invention, the permanent magnet is obtained by arranging diffusion sources on the surface of a substrate of a NdFeB magnet and then subjecting it to a diffusion heat treatment.
[0025] Preferably, the oxygen content of the matrix of the NdFeB magnet is below 2000 ppm. The inventors have found that when the oxygen content of the matrix of the NdFeB magnet is too high, the effect of the diffusion heat treatment is poor.
[0026] Preferably, the diffusion source includes at least Mn and heavy rare earth, wherein the content of Mn does not exceed 20%wt, preferably 0.1-20wt%, for example 0.1wt%, 0.5wt%, 1wt%, 5wt%, 10wt%, 15wt%, 20wt%. The inventors found that when the content of Mn in the diffusion source exceeds 20%wt, too much Mn will lead to a decrease in the concentration of heavy rare earth in the diffusion source, affecting the diffusion efficiency; when Mn is too little, the heavy rare earth content in a local area of the matrix of the NdFeB magnet is too high, the grain reaction between the heavy rare earth and the surface of the matrix is intensified, the effective diffusion depth is reduced, and the difference in coercive force between the inside and the surface of the magnet is increased.
[0027] According to an embodiment of the present invention, the diffusion heat treatment includes at least two stages of heat treatment.
[0028] Preferably, the heat treatment includes first performing a first stage heat treatment and then performing a second stage heat treatment.
[0029] Further, the conditions of the first stage heat treatment include: the temperature of the first stage heat treatment is 800-1000°C, such as 850-950°C, and exemplarily 900°C; the heat treatment time is at least 3h, such as 3-30h, and preferably 3-35h.
[0030] Further, the conditions of the second stage heat treatment include: the temperature of the second stage heat treatment is 400-650°C, such as 450-600°C, and exemplarily 400°C, 500°C, and 600°C; the time of heat treatment is 1-15h, such as 2-8h, and exemplarily 3h, 5h, and 7h.
[0031] According to an embodiment of the present invention, before arranging the diffusion source, the substrate of the NdFeB magnet can also be subjected to a blackening treatment. Further, the conditions for the blackening treatment are: the magnet is subjected to a blackening treatment in an atmospheric atmosphere, the blackening temperature is 200-500°C, and the blackening time is 3-60 minutes.
[0032] According to an exemplary solution of the present invention, the permanent magnet is obtained by subjecting the substrate of the NdFeB magnet to a blackening treatment, arranging diffusion sources on the surface of the blackened substrate, and subjecting the substrate to a heat treatment.
[0033] The present invention also provides a method for manufacturing the rare earth permanent magnet, the method comprising the following steps:
[0034] (1) preparing a matrix of a neodymium iron boron magnet;
[0035] (2) Preparing a diffusion source, wherein the diffusion source comprises at least Mn and a substance containing a heavy rare earth element.
[0036] (3) Arranging the diffusion source described in step (2) on the surface of the substrate, and obtaining the rare earth magnet after diffusion heat treatment.
[0037] According to an embodiment of the present invention, in step (1), the substrate of the NdFeB diffused magnet may be a substrate known in the art, such as a substrate prepared by raw materials known in the art.
[0038] Preferably, the raw materials of the matrix include R, Fe, B, and optionally include or exclude Co and / or M, wherein R and M have the meanings as described above. Exemplarily, the raw materials of the matrix include 27% PrNd, 4% Dy, 2% Co, 0.1% Cu, 0.1% Ga, 0.4% Al%, 0.1% Zr, 1% B, and the balance Fe.
[0039] According to an embodiment of the present invention, the oxygen content of the matrix is below 2000 ppm.
[0040] According to an embodiment of the present invention, in step (1), the preparation method of the matrix of the NdFeB magnet includes: smelting, powder making, pressing, and sintering. In the present invention, the smelting, powder making, pressing, and sintering can be performed by methods known in the art as long as the matrix can be obtained.
[0041] Exemplarily, the preparation method of the matrix of the NdFeB magnet includes: melting the raw materials of the NdFeB magnet and obtaining alloy flakes by rapid solidification and spinning; subjecting the alloy flakes to hydrogen absorption treatment (hydrogen absorption pressure is, for example, 0.2 MPa) and air flow milling to obtain alloy powder (for example, SMD = 2.8 μm); orienting the alloy powder in a magnetic field, controlling the orientation field strength to 2T, and then isostatically pressing at 170 MPa to obtain a green compact, and subjecting the green compact to vacuum sintering treatment (sintering temperature is, for example, 1065°C) to obtain the matrix.
[0042] According to an embodiment of the present invention, in step (1), the substrate may be subjected to a blackening treatment. Further, the conditions of the blackening treatment are: in an atmospheric atmosphere, the blackening temperature is 200-500° C., and the blackening time is 3-60 min.
[0043] According to an embodiment of the present invention, in step (2), the content of Mn in the diffusion source is 0.01-20%, preferably 0.1-20%, for example 5%, 10%, 15%.
[0044] According to an embodiment of the present invention, in step (2), in the diffusion source, the substance containing heavy rare earth elements is selected from pure metals of heavy rare earth and / or compounds of heavy rare earth metals, preferably pure metals of heavy rare earth.
[0045] Preferably, the heavy rare earth metal compound is at least one selected from heavy rare earth fluorides, heavy rare earth oxides, heavy rare earth hydrides, and heavy rare earth oxyfluorides.
[0046] According to an embodiment of the present invention, the present invention does not specifically limit the preparation method of the diffusion source in step (2), as long as the diffusion source can be obtained. Exemplarily, the preparation method of the diffusion source includes: preparing a diffusion source containing Mn and a diffusion source containing a heavy rare earth element respectively, and mixing the two to obtain the diffusion source. Exemplarily, the preparation method of the diffusion source includes: melting an alloy containing Mn and a heavy rare earth element, casting an ingot and preparing the diffusion source.
[0047] According to an embodiment of the present invention, in step (3), the arrangement may be to arrange the diffusion source on the surface of the substrate by a method known in the art, such as at least one selected from thermal spraying, evaporation, coating, magnetron sputtering, burying, printing and the like. Exemplarily, the arrangement method includes: arranging the powder containing heavy rare earth and Mn on the substrate surface of the magnet by coating. Exemplarily, the arrangement method includes: arranging the alloy containing heavy rare earth and Mn on the substrate surface of the magnet by magnetron sputtering.
[0048] According to an embodiment of the present invention, in step (3), the diffusion heat treatment is performed under vacuum or inert gas atmosphere.
[0049] According to an embodiment of the present invention, in step (3), the diffusion heat treatment can be performed by methods known in the art.
[0050] According to an embodiment of the present invention, in step (3), the diffusion heat treatment includes at least two stages of heat treatment.
[0051] Preferably, the diffusion heat treatment includes first performing a first stage heat treatment and then performing a second stage heat treatment.
[0052] Further, the conditions of the first stage heat treatment include: the temperature of the first stage heat treatment is 800-1000°C, such as 850-950°C, and exemplarily 900°C; the heat treatment time is at least 3h, such as 3-30h, and preferably 3-35h.
[0053] Further, the conditions of the second stage heat treatment include: the temperature of the second stage heat treatment is 400-650°C, such as 450-600°C, and exemplarily 400°C, 500°C, and 600°C; the time of heat treatment is 1-10h, such as 2-8h, and exemplarily 3h, 5h, and 7h.
[0054] According to an exemplary embodiment of the present invention, the manufacturing method includes:
[0055] (1') preparing a substrate of a NdFeB magnet and performing a blackening treatment on the substrate;
[0056] (2') preparing a diffusion source, wherein the diffusion source comprises at least Mn and a substance containing a heavy rare earth element, or optionally comprises or excludes M;
[0057] (3') Arranging the diffusion source described in step (2') on the surface of the substrate after blackening treatment in step (1'), and obtaining the rare earth magnet after diffusion heat treatment.
[0058] The inventors have conducted extensive research to solve the above problems and found that when the above manufacturing method is used to prepare rare earth permanent magnets, especially after the matrix of the permanent NdFeB magnet is subjected to diffusion source arrangement and diffusion heat treatment, the heavy rare earth elements diffuse from the surface of the matrix of the permanent NdFeB magnet into the interior of the matrix of the permanent NdFeB magnet, and a rare earth permanent magnet satisfying the above formulas (1) and (2) can be obtained. The enrichment of heavy rare earth on the surface of the permanent NdFeB magnet is greatly reduced, more heavy rare earth is evenly diffused into the interior of the magnet, the coercive force of the diffused magnet is increased, and the coercive force difference between the surface and the core of the permanent magnet is reduced. This is because during the diffusion process, the degree of reaction between the diffusion source and the surface main phase grains of the matrix of the NdFeB magnet is reduced, that is, under the same conditions, more heavy rare earth elements diffuse along the grain boundaries into the interior of the matrix of the NdFeB magnet instead of reacting with the grains on the surface of the matrix themselves. Therefore, the utilization rate of heavy rare earths in the diffusion process is significantly improved, and the enrichment of heavy rare earths on the surface of the permanent magnet obtained after diffusion is reduced. Therefore, the Hcj difference between the surface and the core of the rare earth permanent magnet of the present invention is reduced.
[0059] The inventors found that too low a diffusion temperature during diffusion heat treatment will cause the diffusion rate of the diffusion source in the matrix of the NdFeB magnet to decrease, affecting the diffusion efficiency; while too high a diffusion temperature during diffusion heat treatment will cause the grains to form too much liquid phase at high temperature, and the reaction of the liquid phase with the diffusion source will intensify. The heavy rare earth diffusion source cannot sufficiently diffuse into the core of the matrix of the NdFeB magnet, resulting in an increase in the difference in coercive force between the interior and surface of the permanent magnet, affecting the use of the permanent magnet in the motor.
[0060] It is known in the art that the diffusion process of NdFeB magnets includes the melting of diffusion sources, the reaction of diffusion sources with magnet grains and grain boundaries, and the diffusion of diffusion sources along grain boundaries into the matrix of NdFeB magnets. The inventors have found through experiments that when Mn is added to the heavy rare earth diffusion source, since the melting point of Mn is 1244°C, it is close to the melting point of heavy rare earth (for example, the melting point of Tb is 1172°C, and the melting point of Dy is 1412°C), and when the content of Mn in the diffusion source is 0-20wt%, the melting point of the composite diffusion source is still close to the original heavy rare earth. Under this condition, the diffusion temperature of the composite diffusion source can be close to the diffusion temperature of the heavy rare earth diffusion source. Therefore, there is no problem of transition melting of grain boundary phase caused by too high diffusion temperature or a decrease in the diffusion rate of heavy rare earth elements caused by too low diffusion temperature. In addition, during the diffusion process, due to the introduction of Mn in the diffusion source, the heavy rare earth content at the diffusion interface of the magnet can be relatively reduced, preventing the heavy rare earth produced by supersaturated diffusion on the surface of the matrix of the NdFeB magnet in a short period of time from reacting rapidly with the main phase grains, and even producing an inverse core-shell structure, causing a large amount of heavy rare earth in the diffusion source to be consumed on the surface of the matrix of the NdFeB magnet and failing to successfully and effectively diffuse along the grain boundary into the interior of the magnet. It should be noted that it should be understood in the art that the diffusion temperature refers to the temperature during the diffusion heat treatment.
[0061] The inventors also found that the blackening treatment further slowed down the reaction between the grains on the surface of the NdFeB magnet matrix and the diffusion source, allowing more diffusion sources to enter the core of the NdFeB magnet matrix, reducing the difference in coercive force between the surface and the core of the permanent magnet. The inventors found that if the blackening temperature is too high or the blackening time is too long, the grains on the surface of the NdFeB magnet matrix will be over-oxidized, and the residual magnetism of the NdFeB magnet matrix will be reduced; while if the blackening temperature is too low or the blackening time is too short, the grains on the surface of the NdFeB magnet matrix are not fully oxidized, and some grains will still react quickly with the diffusion source.
[0062] In addition, the present invention not only improves the heavy rare earth distribution and Hcj distribution of the permanent magnet by arranging the diffusion source on the surface of the substrate of the NdFeB magnet and performing diffusion heat treatment, but also has a certain effect on the corrosion resistance and mechanical properties of the permanent magnet. This is mainly because when the diffusion source of the present invention is diffused, the heavy rare earth can be more evenly distributed in the magnet, especially in the surface of the magnet and the area of the core of the magnet, so along the diffusion direction, the composition and organizational consistency of the magnet are improved.
[0063] The present invention also provides a rare earth permanent magnet prepared by the above manufacturing method.
[0064] The present invention also provides application of the rare earth permanent magnet, preferably in a motor.
[0065] Beneficial Effects
[0066] The rare earth permanent magnet prepared by the manufacturing method of the present invention can allow more heavy rare earth elements to diffuse into the magnet core along the grain boundary, improve the Hcj distribution of the permanent magnet, and also improve the corrosion resistance and mechanical properties of the permanent magnet. DETAILED DESCRIPTION
[0067] The technical scheme of the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.
[0068] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.
[0069] In the following embodiments, magnets at different positions of the magnet after diffusion treatment are taken as samples to be tested, and the following tests are performed:
[0070] 1. Magnetic property test: 1mm-1mm-1mm standard samples are processed on the surface and geometric center of the diffused magnet, and the magnetic properties are tested on a pulse magnetic field meter (PFM).
[0071] 2. Composition test: After diffusion, the magnet is divided into two parts in the diffusion direction, and the contents of Mn and heavy rare earth on the surface and in the center of the permanent magnet are measured using an X-ray fluorescence spectrometer (XRF), wherein the Mn content on the surface of the permanent magnet is recorded as x1, and the heavy rare earth content is recorded as y1, and the Mn content from the surface of the permanent magnet to 500 μm inside the magnet is recorded as x2, and the heavy rare earth content is recorded as y2.
[0072] 3. Impact absorption energy test: Test the impact absorption energy of the diffused sample (size is about 55mm-10mm-6mm) on an impact testing machine. Test 5 times and take the average value.
[0073] Example 1
[0074] The manufacturing method of rare earth permanent magnet is as follows:
[0075] (1) Preparation of the matrix of sintered NdFeB magnets:
[0076] The raw materials of the sintered NdFeB permanent magnet include, by weight percentage, 27% PrNd, 4% Dy, 2% Co, 0.1% Cu, 0.1% Ga, 0.4% Al, 0.1% Zr, 1% B, and the remainder Fe. The above raw materials are used to make alloy flakes by a rapid solidification strip throwing method.
[0077] The quick-setting flakes obtained above are subjected to hydrogen absorption treatment, with a hydrogen absorption pressure of 0.2MPa, and then subjected to jet milling to obtain a powder with SMD=2.8μm, and an antioxidant fatty acid ester accounting for 0.05wt% of the total raw material is added and mixed evenly to obtain alloy fine powder. The above alloy fine powder is subjected to orientation pressing in a magnetic field, with the orientation field strength controlled to be 2T, and then subjected to isostatic pressing at 170MPa to obtain a compact. The above compact is placed in a vacuum heat treatment sintering, and the sintering temperature is controlled to be 1065℃.
[0078] The sintered compact is machined into a matrix with a size of 55 mm*10 mm*6 mm, wherein the dimension in the orientation direction is 6 mm, and the oxygen content of the matrix is below 2000 ppm.
[0079] (2) Preparation of diffusion source:
[0080] After Tb powder and Mn powder were mixed in a ratio of 95% to 5% by weight, 1% of 4-hexylresorcinol antioxidant and 5% of ethanol were added to form a slurry.
[0081] (3) Arrangement of diffusion source and diffusion heat treatment:
[0082] The substrate of step (1) was subjected to blackening treatment in air at a temperature of 300° C. for 40 min;
[0083] The slurry of step (2) is coated on the surface of the substrate and subjected to diffusion heat treatment. The diffusion heat treatment process includes: a primary heat treatment at a diffusion temperature of 940°C and a heat treatment time of 30 hours; followed by a secondary heat treatment at 500°C and a heat treatment time of 10 hours to obtain the rare earth permanent magnet of this embodiment.
[0084] The magnetic properties and mechanical properties of the rare earth magnet of this embodiment were tested using the test method described above.
[0085] Example 2
[0086] The manufacturing method of rare earth permanent magnet is as follows:
[0087] (1) Preparation of sintered NdFeB magnet matrix:
[0088] The raw materials of the sintered NdFeB permanent magnet include, by weight percentage, 27% PrNd, 4% Dy, 2% Co, 0.1% Cu, 0.1% Ga, 0.4% Al, 0.1% Zr, 1% B, and the remainder Fe. The above raw materials are used to make alloy flakes by a rapid solidification strip throwing method.
[0089] The quick-setting flakes obtained above are subjected to hydrogen absorption treatment, with a hydrogen absorption pressure of 0.2MPa, and then subjected to jet milling to obtain a powder with SMD=2.8μm, and 0.05wt% of antioxidant fatty acid ester accounting for the total amount of raw materials is added and mixed uniformly to obtain alloy fine powder. The above alloy fine powder is subjected to orientation pressing in a magnetic field, with the orientation field strength controlled to be 2T, and then subjected to isostatic pressing at 170MPa to obtain a compact. The above compact is placed in a vacuum heat treatment sintering, and the sintering temperature is controlled to be 1065℃.
[0090] The sintered compact is machined into a base with a size of 55 mm*10 mm*6 mm, wherein the dimension in the orientation direction is 6 mm.
[0091] (2) Preparation of diffusion source:
[0092] After Tb powder and Mn powder were mixed in a ratio of 85% to 15% by weight, 1% of 4-hexylresorcinol antioxidant and 5% of ethanol were added to form a slurry.
[0093] (3) Arrangement of diffusion source and diffusion heat treatment:
[0094] The substrate of step (1) was subjected to a blackening treatment in air at a temperature of 300° C. and a treatment time of 40 min under an atmospheric atmosphere.
[0095] The slurry of step (2) is coated on the surface of the substrate and subjected to diffusion heat treatment. The diffusion heat treatment process includes a primary heat treatment at a diffusion temperature of 940°C and a heat treatment time of 30 hours; and a subsequent secondary heat treatment at 500°C and a heat treatment time of 10 hours to obtain the rare earth permanent magnet of this embodiment.
[0096] The magnetic and mechanical properties of the permanent magnet of this embodiment are tested using the test method described above.
[0097] Example 3
[0098] The manufacturing method of rare earth permanent magnet is as follows:
[0099] (1) Preparation of sintered NdFeB magnet matrix:
[0100] The raw materials of the sintered NdFeB permanent magnet include, by weight percentage, 27% PrNd, 4% Dy, 2% Co, 0.1% Cu, 0.1% Ga, 0.4% Al, 0.1% Zr, 1% B, and the remainder Fe. The above raw materials are used to make alloy flakes by a rapid solidification strip throwing method.
[0101] The quick-setting flakes obtained above are subjected to hydrogen absorption treatment, with a hydrogen absorption pressure of 0.2MPa, and then subjected to jet milling to obtain a powder with SMD=2.8μm, and an antioxidant fatty acid ester accounting for 0.05wt% of the total raw material is added to mix the alloy fine powder evenly. The above alloy fine powder is subjected to orientation pressing in a magnetic field, with the orientation field strength controlled to be 2T, and then subjected to isostatic pressing at 170MPa to obtain a compact. The above compact is placed in a vacuum heat treatment sintering, and the sintering temperature is controlled to be 1065℃.
[0102] The sintered compact is machined into a base with a size of 55 mm*10 mm*6 mm, wherein the dimension in the orientation direction is 6 mm.
[0103] (2) Preparation of diffusion source: Tb and Mn were mixed in a weight percentage ratio of 85% to 15% and melted to prepare diffusion source powder, and 1% 4-hexylresorcinol antioxidant and 5% ethanol were added to mix into slurry.
[0104] (3) Arrangement of diffusion source and diffusion heat treatment:
[0105] The substrate of step (1) was subjected to blackening treatment in air at a treatment temperature of 300° C. and a treatment time of 40 min.
[0106] The slurry of step (2) is coated on the surface of the substrate and subjected to diffusion heat treatment. The diffusion heat treatment process includes: a primary heat treatment at a diffusion temperature of 940°C and a heat treatment time of 30 hours; followed by a secondary heat treatment at 500°C and a heat treatment time of 10 hours to obtain the rare earth permanent magnet of this embodiment.
[0107] The magnetic and mechanical properties of the permanent magnet of this embodiment are tested using the test method described above.
[0108] Example 4
[0109] The manufacturing method of rare earth permanent magnet is as follows:
[0110] (1) Preparation of sintered NdFeB magnet matrix:
[0111] The raw materials of the sintered NdFeB permanent magnet include, by weight percentage, 27% PrNd, 4% Dy, 2% Co, 0.1% Cu, 0.1% Ga, 0.4% Al, 0.1% Zr, 1% B, and the remainder Fe. The above raw materials are used to make alloy flakes by a rapid solidification strip throwing method.
[0112] The quick-setting flakes obtained above are subjected to hydrogen absorption treatment, with a hydrogen absorption pressure of 0.2MPa, and then subjected to jet milling to obtain a powder with SMD=2.8μm, and an antioxidant fatty acid ester accounting for 0.05wt% of the total raw material is added to mix the alloy fine powder evenly. The above alloy fine powder is subjected to orientation pressing in a magnetic field, with the orientation field strength controlled to be 2T, and then subjected to isostatic pressing at 170MPa to obtain a compact. The above compact is placed in a vacuum heat treatment sintering, and the sintering temperature is controlled to be 1065℃.
[0113] The sintered compact is machined into a base with a size of 55 mm*10 mm*6 mm, wherein the dimension in the orientation direction is 6 mm.
[0114] (2) Preparation of diffusion source:
[0115] Terbium fluoride and Mn were arranged and melted in a weight percentage ratio of 95% to 5% to prepare diffusion source powder, and 1% of 4-hexylresorcinol antioxidant and 5% of ethanol were added to mix into slurry.
[0116] (3) Arrangement of diffusion source and diffusion heat treatment:
[0117] The substrate of step (1) was subjected to blackening treatment in air at a treatment temperature of 300° C. and a treatment time of 40 min.
[0118] The slurry of step (2) is coated on the surface of the substrate and subjected to diffusion heat treatment. The diffusion heat treatment process includes: a primary heat treatment at a diffusion temperature of 940°C and a heat treatment time of 30 hours; followed by a secondary heat treatment at 500°C and a heat treatment time of 10 hours to obtain the rare earth permanent magnet of this embodiment.
[0119] The magnetic and mechanical properties of the magnet of this embodiment were tested using the test method described above.
[0120] Example 5
[0121] The manufacturing method of this embodiment is basically the same as that of Embodiment 1, except that, before arranging the diffusion source, a pickling treatment is used instead of a blackening treatment.
[0122] Comparative Example 1
[0123] The manufacturing method of this comparative example is basically the same as that of Example 1, except that in step (2), the diffusion source is 100% Tb.
[0124] Comparative Example 2
[0125] The manufacturing method of this comparative example is basically the same as that of Example 1, except that in step (2), the diffusion sources are 95% Tb and 5% Al.
[0126] Comparative Example 3
[0127] The manufacturing method of this comparative example is basically the same as that of Example 1, except that in step (2), the diffusion sources are 95% Tb and 5% Ti.
[0128] Comparative Example 4
[0129] The manufacturing method of this comparative example is basically the same as that of Example 1, except that in step (2), the diffusion source is 75% Tb and 25% Mn.
[0130] Comparative Example 5
[0131] The manufacturing method of this comparative example is basically the same as that of Example 1, except that in step (2), the diffusion source is 95% terbium fluoride and 5% Al.
[0132] Comparative Example 6
[0133] The manufacturing method of this comparative example is basically the same as that of Example 1, except that in step (2), the diffusion source is 90% terbium fluoride, 5% Mn and 5% Al.
[0134] Comparative Example 7
[0135] The manufacturing method of this comparative example is basically the same as that of Example 1, except that in step (1), the raw materials for sintering NdFeB permanent magnets include: PrNd is 27%, Dy is 4%, Co is 2%, Cu is 0.1%, Ga is 0.1%, Al% is 0.4%, Zr is 0.1%, B is 1%, Mn is 0.2%, and Fe is the remainder.
[0136] Table 1 is a summary table of the distribution of Mn and Tb elements at different positions of the permanent magnets of the above embodiments and comparative examples, including the Mn and Tb contents at the surface and 500 μm from the surface, and whether formula (1) is satisfied.
[0137] Table 1 Summary of Mn and Tb element distribution at different positions of permanent magnets
[0138]
[0139] Table 2 is a summary table of the surface coercivity, core coercivity, and surface and core magnetic properties of the permanent magnets of the above embodiments and comparative examples, including coercivity difference, impact absorption energy of the magnets, and other properties.
[0140] Table 2 Summary of magnetic properties
[0141]
[0142] In summary, it can be concluded from Table 1 and Table 2 that: by introducing an appropriate amount of Mn into the diffusion source in Examples 1-5, the heavy rare earth concentration difference y1 / y2 in the rare earth permanent magnet prepared by the present invention is smaller, the uniformity of the magnetic properties of the magnet is improved, the coercive force difference z1-z2 between the surface and the core of the magnet is smaller, and the impact toughness (impact absorption work) of the magnet is also improved.
[0143] By comparing Examples 1 and 5, it can be seen that since no blackening treatment is performed before arranging the diffusion sources, the grains and grain boundaries on the surface of the substrate react quickly with the diffusion sources, thereby relatively reducing the diffusion sources entering the substrate. Therefore, the uniformity of the permanent magnet is slightly lower than that of Example 1.
[0144] By comparing Examples 1 and 4, it can be seen that the uniformity of the permanent magnet is slightly reduced when terbium fluoride is used as the diffusion source.
[0145] It can be seen from Comparative Examples 1 and 4 that when the diffusion source does not contain Mn or the Mn content is higher than 20%, the difference in coercive force between the surface layer and the core of the permanent magnet increases, and the uniformity of the permanent magnet deteriorates.
[0146] Comparative Examples 2, 5 and 6 show that since the diffusion source contains Al element with a lower melting point, the surface grains of the magnet react excessively with the diffusion source to form an inverse core-shell structure, resulting in a decrease in the surface coercive force of the magnet.
[0147] It can be seen from Comparative Example 3 that when the diffusion source contains the high melting point Ti element, it is difficult for the heavy rare earth to effectively diffuse into the interior of the magnet, so the core coercive force of the magnet is reduced and the difference between the inside and outside increases.
[0148] Regarding Comparative Example 7, Mn is added to the diffusion substrate and is uniformly distributed in the permanent magnet. There is no Mn concentration gradient inside the permanent magnet. Therefore, although the diffusion treatment is performed, the diffusion effect is not as good as that of Example 1.
[0149] The above is a description of the exemplary embodiments of the present invention. However, the protection scope of the present application is not limited to the above embodiments. Any modification, equivalent substitution, improvement, etc. made by those skilled in the art within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A rare earth permanent magnet, characterized in that: The rare earth permanent magnet is obtained by arranging a diffusion source on the surface of a substrate of a neodymium iron boron magnet and then subjecting it to a diffusion heat treatment; the diffusion source is Mn and a substance containing a heavy rare earth element, wherein the content of Mn does not exceed 20wt%; The rare earth permanent magnet includes R2T 14 The main phase structure of B grains, where R is a rare earth element; T comprises at least Mn, Fe, and optionally a transition metal including Co; B is boron; The rare earth permanent magnet also includes Mn and heavy rare earth elements diffused in the grain boundaries; the heavy rare earth element is at least one of Dy, Ho, and Tb; The thickness of the rare earth permanent magnet is m, and the thickness of the rare earth permanent magnet is m≤15 mm; the Mn content at the surface of the rare earth permanent magnet is x1, the heavy rare earth element content at the surface is y1, the Mn content 500 μm away from the surface is x2, and the heavy rare earth element content 500 μm away from the surface is y2, wherein x1>x2 and y1>y2; The coercive force at the surface of the rare earth permanent magnet is z1, and the coercive force at the core of the rare earth permanent magnet is z2, z1>z2; The rare earth permanent magnet satisfies the following equations (1) and (2): x1 / x2≥y1 / y2 (1) [2*x1 / x2-(z1-z2) / 2 / m]≥0(2).
2. The rare earth permanent magnet according to claim 1, characterized in that: The R is selected from Nd, and optionally contains or does not contain at least one of Pr, Dy, Tb, Ho, Ce, and Gd; The rare earth permanent magnet also includes M; M is selected from at least one of aluminum, titanium, copper, gallium, zirconium and niobium.
3. The rare earth permanent magnet according to claim 1, characterized in that: The oxygen content of the rare earth permanent magnet is below 2000 ppm.
4. The rare earth permanent magnet according to claim 1, characterized in that: The oxygen content in the matrix of the NdFeB magnet is below 2000 ppm; In the diffusion source, the content of Mn is 0.1-20wt%; The diffusion heat treatment includes at least two stages of heat treatment.
5. The rare earth permanent magnet according to claim 4, characterized in that: The heat treatment includes first performing a first stage heat treatment and then performing a second stage heat treatment; The conditions of the first stage heat treatment include: the temperature of the first stage heat treatment is 800-1000°C; the heat treatment time is at least 3h; The conditions of the second stage heat treatment include: the temperature of the second stage heat treatment is 400-650° C.; and the time of the heat treatment is 1-15 hours.
6. The rare earth permanent magnet according to claim 1, characterized in that: Before arranging the diffusion source, the substrate of the NdFeB magnet is also subjected to a blackening treatment; the conditions for the blackening treatment are: the magnet is subjected to a blackening treatment in an atmospheric atmosphere, the blackening temperature is 200-500° C., and the blackening time is 3-60 min.
7. The method for manufacturing a rare earth permanent magnet according to any one of claims 1 to 6, characterized in that: The manufacturing method comprises the following steps: (1) preparing a matrix of a neodymium iron boron magnet; (2) preparing a diffusion source, wherein the diffusion source is Mn and a substance containing a heavy rare earth element; (3) arranging the diffusion source described in step (2) on the surface of the substrate, and obtaining the rare earth permanent magnet after diffusion heat treatment; The raw materials of the matrix include R, Fe, B, and optionally include Co and / or M.
8. The manufacturing method according to claim 7, characterized in that: The oxygen content of the matrix is below 2000 ppm; In step (1), the preparation method of the matrix of the NdFeB magnet includes: smelting, powder making, pressing and sintering; In step (1), the substrate is also subjected to a blackening treatment; the conditions of the blackening treatment are: in an atmospheric atmosphere, the blackening temperature is 200-500° C., and the blackening time is 3-60 min.
9. The manufacturing method according to claim 7, characterized in that: In step (2), the content of Mn in the diffusion source is 0.01-20%; In step (2), in the diffusion source, the substance containing heavy rare earth elements is selected from pure heavy rare earth metals and / or compounds of heavy rare earth metals; The heavy rare earth metal compound is selected from at least one of heavy rare earth fluorides, heavy rare earth oxides, heavy rare earth hydrides, and heavy rare earth oxyfluorides.
10. The manufacturing method according to claim 7, characterized in that: In the diffusion source, the content of Mn is 0.1-20%; The substance containing heavy rare earth elements is pure metal of heavy rare earth.
11. The manufacturing method according to claim 7, characterized in that: In step (3), the arranging method includes arranging the diffusion source on the surface of the substrate.
12. The manufacturing method according to claim 11, characterized in that: The arrangement method is selected from at least one of thermal spraying, evaporation, coating, magnetron sputtering, burying and printing.
13. The manufacturing method according to claim 7, characterized in that: In step (3), the diffusion heat treatment is performed in a vacuum or inert gas atmosphere; In step (3), the diffusion heat treatment includes at least two stages of heat treatment.
14. The manufacturing method according to claim 7, characterized in that: The diffusion heat treatment includes first performing a first stage heat treatment and then performing a second stage heat treatment; The conditions of the first stage heat treatment include: the temperature of the first stage heat treatment is 800-1000°C; the heat treatment time is at least 3h; The conditions of the second stage heat treatment include: the temperature of the second stage heat treatment is 400-650° C.; and the time of the heat treatment is 1-10 hours.
15. Use of the rare earth permanent magnet according to any one of claims 1 to 6 in an electric motor.
Citation Information
Patent Citations
Preparation process for improving high temperature resistance performance and ultralow weight loss of neodymium iron boron magnet
CN109411226A
Method for manufacturing rare earth magnet
JP2021048347A
Method of producing r-t-b sintered magnet
US20130299050A1
Method for Manufacturing Rare Earth Sintered Magnet
US20220148801A1
Method for preparing r-t-b permanent magnet
WO2016095869A1